STUDY OF ISLAMIC MONETARY POLICY LITERATURE: (Effectiveness of Real Sector Performance Strengthening) - Andri Soemitra; Rifki Ismal; Abi Waqqosh; Heny Liya Hasibuan; Husni Pasarela (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
The purpose of this article is to analyze how effective the Islamic monetary policy system is in maintaining or improving the performance of the real sector. And how Islamic monetary economic policy is able to maintain stability between the real sector and the monetary sector compared to the implementation of conventional monetary economic policy. The research design uses library research design (library study design). namely a research by studying, researching and reviewing relevant library materials. The data collection method used in this study is documentation, namely the method of data collection by reviewing various books (literature) that are relevant to the subject matter to be studied. With data analysis techniques using content analysis techniques, (Content Analysis) is research that is in-depth discussion of the contents of a written or printed information in the mass media. Which in the analysis it was found that Islamic monetary policy is effective in improving the performance of the real sector.